Pitch perception and production in congenital amusia: Evidence from Cantonese speakers - Chan, Alice Hiu Dan (2017)
This study investigated pitch perception and production in speech and music in individuals with congenital amusia (a disorder of musical pitch processing) who are native speakers of Cantonese, a tone language with a highly complex tonal system. Sixteen Cantonese-speaking congenital amusics and 16 controls performed a set of lexical tone perception, production, singing, and psychophysical pitch threshold tasks. Their tone production accuracy and singing proficiency were subsequently judged by independent listeners, and subjected to acoustic analyses. Relative to controls, amusics showed impaired discrimination of lexical tones in both speech and non-speech conditions. They also received lower ratings for singing proficiency, producing larger pitch interval deviations and making more pitch interval errors compared to controls. Demonstrating higher pitch direction identification thresholds than controls for both speech syllables and piano tones, amusics nevertheless produced native lexical tones with comparable pitch trajectories and intelligibility as controls. Significant correlations were found between pitch threshold and lexical tone perception, music perception and production, but not between lexical tone perception and production for amusics. These findings provide further evidence that congenital amusia is a domain-general language-independent pitch-processing deficit that is associated with severely impaired music perception and production, mildly impaired speech perception, and largely intact speech production.